Effects of CaMKII-Mediated Phosphorylation of Ryanodine Receptor Type 2 on Islet Calcium Handling, Insulin Secretion, and Glucose Tolerance - Dixit, Sayali S. (Public Library of Science, 2013)
Altered insulin secretion contributes to the pathogenesis of type 2 diabetes. This alteration is correlated with altered intracellular Ca2+-handling in pancreatic β cells. Insulin secretion is triggered by elevation in cytoplasmic Ca2+ concentration ([Ca2+]cyt) of β cells. This elevation in [Ca2+]cyt leads to activation of Ca2+/calmodulin-dependent protein kinase II (CAMKII), which, in turn, controls multiple aspects of insulin secretion. CaMKII is known to phosphorylate ryanodine receptor 2 (RyR2), an intracellular Ca2+-release channel implicated in Ca2+-dependent steps of insulin secretion. Our data show that RyR2 is CaMKII phosphorylated in a pancreatic β-cell line in a glucose-sensitive manner. However, it is not clear whether any change in CaMKII-mediated phosphorylation underlies abnormal RyR2 function in β cells and whether such a change contributes to alterations in insulin secretion. Therefore, knock-in mice with a mutation in RyR2 that mimics its constitutive CaMKII phosphorylation, RyR2-S2814D, were studied. This mutation led to a gain-of-function defect in RyR2 indicated by increased basal RyR2-mediated Ca2+ leak in islets of these mice. This chronic in vivo defect in RyR2 resulted in basal hyperinsulinemia. In addition, S2814D mice also developed glucose intolerance, impaired glucose-stimulated insulin secretion and lowered [Ca2+]cyt transients, which are hallmarks of pre-diabetes. The glucose-sensitive Ca2+ pool in islets from S2814D mice was also reduced. These observations were supported by immunohistochemical analyses of islets in diabetic human and mouse pancreata that revealed significantly enhanced CaMKII phosphorylation of RyR2 in type 2 diabetes. Together, these studies implicate that the chronic gain-of-function defect in RyR2 due to CaMKII hyperphosphorylation is a novel mechanism that contributes to pathogenesis of type 2 diabetes.